Development and Characterization of an Asymmetric MZI Temperature Sensor Using Polymer Waveguides for Extended Temperature Measurement Scopes - Fumin Liu; Xue Zhang; Tianyue Wang; Guanghao Huang (Photonics)
To meet diverse industrial needs, temperature sensors with a wide measurement range have become a key element. In this paper, we propose an asymmetric Mach–Zehnder interferometer (MZI) temperature sensor based on polymer optical waveguides. Experimental results show that the output interference signal exhibits periodic changes with temperature variations. The device exhibits a temperature measurement range of 120 °C and a sensitivity of 0.27 rad/°C. This study provides an effective new approach for developing high-performance, low-cost temperature sensors suitable for an extended temperature measurement range.